The use of planar bone scintigraphy and HiSPECT for diagnosis of primary and concomitant flexor enthesopathy in the canine elbow - de Bakker, E.; Peremans, K.; Vermeire, S.; Vandermeulen, E.; Dobbeleir, A.; Dik, K. J.; Gielen, I.; Saunders, J. H.; Van Ryssen, B. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
Objective: To investigate the possibilities and limitations of planar bone scintigraphy and high resolution single photon emission computed tomography (HiSPECT) to diagnose flexor enthesopathy and to distinguish primary flexor enthesopathy from the concomitant form.Materials and methods: A prospective study of 46 dogs with primary flexor enthesopathy, concomitant flexor enthesopathy, medial coronoid disease, and normal elbows was performed. All dogs underwent planar bone scintigraphy and HiSPECT imaging. The obtained images were visually scored for increased radiopharmaceutical uptake in the medial humeral epicondylar and medial coronoid process region using a score from 1-3.Results: Planar bone scintigraphy demonstrated increased radiopharmaceutical uptake in all diseased elbow joints, except for one. HiSPECT demonstrated increased radiopharmaceutical uptake of the medial humeral epicondyle in nearly all clinically affected joints with primary and concomitant flexor enthesopathy. Additional uptake of the medial coronoid process was recorded in all clinically affected joints with concomitant flexor enthesopathy and in six out of 18 with primary flexor enthesopathy. No difference in intensity of the uptake was noticed.Clinical significance: Planar bone scintigraphy allows the attribution of lameness to the elbow joint in cases of primary flexor enthesopathy with minimal or even absent radiographic changes. The more detailed HiSPECT enables the localization of pathology within the elbow joint and is a sensitive technique to detect flexor enthesopathy. However HiSPECT is insufficient to distinguish primary from concomitant flexor enthesopathy.
Keywords: Planar bone scintigraphy; HiSPECT; flexor enthesopathy; diagnosis; canine elbow